Investigation and Filtering of Harmonic Currents in Hybrids Renewable Energy System - Djeghader, Yacine; Boumous,Zouhir; Boumous,Samira (PRZEGLĄD ELEKTROTECHNICZNY,, 2023)
Abstract. This study investigates and filters harmonic currents generated by a hybrid system with a storage system (photovoltaic-wind-battery) for Household Applications. In this paper, we prefer to use passive filtering to mitigate the harmonic currents especially the passive tuned filter (single and multiple). This method is the most used because it's cheap and effective. The hybrid system studied is used for power supply household applications. This modern system can improve efficiency, reliability, and security while reducing operating costs and offering flexibility. For better working for our system, we use two commands called maximum power point tracking command (MPPT); one for photovoltaic panels, and the second for the wind system, the pulse width modulation control (PWM) for the inverter, and for the control the battery we apply a DC/DC buck-boost. The simulation results obtained with filtering show the improvement of current waveforms and acceptable values of total harmonic distortion (THD).